Database Transaction Processing with Effective Locking Mechanism for Consistency in Cloud Database - Begum, A. Aasha; Chitra, K (International Journal of Computer Sciences and Engineering, 2025)
The cloud infrastructure provides Database Management System as a service with scalability and elasticity. Cloud DBMS is a less expensive platform for managing our data resources. Cloud data are replicated for high data availability. Concurrent transactions are done in the cloud database. Database users expect that data should be consistent when two users access to the same data at the same time and can see the same value. Due to replication of data in cloud environment, data inconsistency may occur between different replicated nodes. Hence Effective locking mechanisms are needed to handle such replicated cloud database. This paper proposes a novel algorithm for transaction processing to solve inconsistency and to control concurrency using lock managers and queue supervisor